An investigation of left–right vocal fold symmetry in rheological and histological properties. (10th August 2018) - Xu, Chet C.; Gao, Ang; Zhang, Song
Abstract : Objectives: The primary objective was to investigate the left–right vocal fold symmetry in rheological and histological properties using a rabbit model. The other objective was to develop statistical models for the comparison of rheological properties between paired vocal folds. Methods: Viscoelastic shear properties of six pairs of vocal fold lamina propria specimens were measured over a frequency range of 1 to 250 Hz by a linear, controlled‐strain, simple‐shear rheometer. The rheological data of the left and right vocal folds was statistically compared using the mixed‐effects model approach. Six additional rabbit larynges were histologically analyzed for left–right symmetry in distribution patterns and relative densities of major extracellular matrix constituents. Results: There were no significant differences in elastic shear modulus ( P = 0.1069) and dynamic viscosity ( P = 0.944) of the lamina propria between the two vocal folds of the same larynx. Left–right vocal fold symmetry in densities and distribution patterns of the key molecular constituents was also demonstrated in histological results. Conclusion: By showing that the left and right vocal folds were rheologically and histologically symmetrical in rabbit, this study validated an underlying assumption made in many previous reports. Statistical models for the analysis of hierarchically correlated left–right vocal fold rheological data were also presented. Level of Evidence: NA. Laryngoscope, 128:E359–E364, 2018